Study on Marketing Margins and Market Structure of Cashewnut in Kerala - Rajasekharan P (Department of Agricultural Economics, College of Horticulture, 1987)
A study on marketing margins and Market Structure of Cashewnut in Kerala was conducted during 1985-’86 season and the main objectives were to analyse the present marketing costs and margins, to evaluate efficiency of transportation, storage, processing and to anlyse the likely impact of changes in marketing organization and structure on pricing efficiency. Two panchayats viz. Enmaje and Kottiyoor from Cannanore district and one panchayat viz. Karupra from Quilon district were selected for the study. Three wards from each panchayath and eight farmers from each ward and altogether 72 farmers were selected randomly. From the selected wards a sample of various intermediaries and few wholesalers from the nearest place were interviewed. Harvesting and marketing season for cashewnuts started by February and continued till May. The farmers in Enmakaje and Karupra panchayats harvested natured nuts and the farmers in Kottiyoor panchayat collected the fallen nuts. The various market functionaries involved in cashewnut marketing were the village merchants, petty traders, itinerant traders, semi-wholesalers, wholesalers and processors. Five marketing channels were identified in Enmakaje panchayat and the first channel viz. Producer-Village merchant-wholesaler-processor was found to be the main channel in moving rawnuts in the panchayat. Ninety two per cent of the farmers sold 72 per cent of the total quantity to buyers within the village and only 8 per cent sold outside the village. The sales of different types of traders to the wholesalers showed that 72.71 per cent of village merchants sold 86.81 per cent of nuts to the wholesalers which indicated a high degree of concentration in the volume of rawnuts purchased. Two marketing channels were identified in Kottiyoor panchayat and the first channel viz. producer- Village merchant- wholesaler – processor was identified as the main channel and eighty seven per cent of farmers sold their produce to the village merchant which constituted 74.31 per cent of total sales of sample. Three marketing channels were identified in Karupra panchayat and the first channel viz. Producer – Village merchant – Wholesaler – Processor was observed to be the main channel in moving nuts and 83.33 per cent of farmers sold 86.68 per cent nuts to village merchants. The market structure indicated large number of buyers at the farmer level, and a possibility of competition among the buyers was identified. Marketing costs of farmers and different agencies were worked out in three panchayats. Drying charges formed the major item of cost for the farmers in Enmakaje and Karupra and cost of transport formed the major cost item of farmers in Kottiyoor panchayat. Cost of transport, loading/unloading and cost of packing material formed the major cost item of various intermediaries in the three panchayats. The cost incurred by the processors were estimated on the basis of information obtained from sample factories in Quilon district and worked out to Rs.337.80 per quintal of rawnuts. Wages formed the major share of processor’s cost which constituted 27.71 per cent of the cost. Total recovery of kernels was estimated as 26.79 per cent and the returns from by-products such as cashewnut shell liquid, shell and skin were computed to Rs. 64.83 per quintal of nuts. Marketing margins were worked out from the stage of farmer sale of nuts to the stage of wholesale of kernels based on the New York market price using a variant of concurrent margin. The processors reaped very high profits of Rs. 356.86 (18.17 per cent of total realization), Rs.373.01 (18.37 per cent) and Rs.522.01 (25.71 per cent) per quintal of nuts in Enmakaje, Kottiyoor and Karupra panchayats, respectively. Marketing margins computed through concurrent margin showed exorbitant profit for the processors and the net margins of processors worked out through lagged margin method by taking into account driage and interest on inventory holding from April to November corresponding to processing period of rawnuts also were in consonance with that of results of concurrent margin method. Net margin of processors through lagged margin method varied from Rs.232.39 to Rs.819.32 (12.47 to 33.43 per cent of total realization) Rs.182.46 to Rs.769.39 (9.79 to 31.40 per cent) and Rs.335.67 to Rs.922.60 (18.01 to 37.65 per cent) per quintal of nuts in Enmakaje, Kottiyoor and Karupra panchayats, respectively from April to November 1986. High margins are a symptom of inefficiency.